Penerapan Reward dan Punishment dalam Peningkatan Pengamalan Sholat Berjama’ah Santri Madrasah Aliyah Pondok Pesantren Al-Hakimiyah Kabupaten Padang Lawas - Hasibuan, Najamuddin; Anhar, Anhar; Hilda, Lelya (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2021)
This study aims to describe the application of reward and punishment to Santri Madrasah Aliyah Pondok Pesantren Al-Hakimiyah Padang Lawas Regency in carrying out congregational prayers. This study uses a qualitative method with a Participatory Action Research (PAR) approach. The data sources used are primary data sources from the Dormitory Trustees, and Aliyah Santri, and secondary data sources are the Leaders, Deputy Principals for Student Affairs, and the Community around Al-Hakimiyah Islamic Boarding School. The instruments used were observations, interviews, and documents for boarding the Al-Hakimiyah Islamic Boarding School.The results showed that the reward method applied at the Al-Hakimiyah Islamic Boarding School was in the form of expressions of pleasure to students who performed congregational prayers, while punishment was applied in the form of calls or reprimands along with advice about the importance of praying in congregation at the mosque. The reward and punishment method is effectively applied to the congregational prayer of aliyah students at the Al-Hakimiyah Islamic Boarding School. This is evidenced by the increase in the practice of praying in congregation for Madrasah Aliyah students. In the first act is 22.5%, in the second act is 32.5%, in the third act is 52.5% and in the fourth act is 80%